Bark! : the science of helping your anxious, fearful, or reactive dog - Todd, Zazie (Greystone Books, 2024)
"Compassionate, practical, and rooted in science, Bark! helps dog owners understand the many factors that might be causing fear within your dog, and how you can help them lead a safe and happy life."--